Polyolefin coated diaphragm with ion selectivity, preparation method and application
By using a porous polyolefin support layer and PIM-based material in the lithium-ion battery separator, the problem that the existing separator cannot achieve lithium ion selective conduction is solved, and the performance of the separator and the service life of the battery are significantly improved.
Patent Information
- Application Number
- CN202510273216.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-10
- Publication Date
- 2025-04-08
AI Technical Summary
The existing lithium-ion battery separators cannot achieve single selective conduction of lithium ions, causing nickel ions and manganese ions in the positive electrode material to pass through the separator, resulting in a gradual attenuation of the battery capacity.
The polyolefin coated membrane is used to form a porous polyolefin support layer and the first and second ion-selective cortexes on both sides. The first and second ion-selective cortexes are composed of intrinsic microporous polymer PIM or its modified material to ensure the permeability of the membrane to lithium ions and the barrier properties to metal ions such as nickel and manganese.
It effectively improves the mechanical properties and heat resistance of the separator, and at the same time greatly reduces the diffusion coefficient for metal ions such as Mn, Ni, and Fe, and extends the service life of lithium-ion batteries.
Smart Images

Figure CN119786889A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium ion battery separators, and in particular to a polyolefin-coated separator with ion selectivity, a preparation method and application thereof. Background Art
[0002] Lithium-ion batteries are widely used in new energy vehicles, electrochemical energy storage, electronic digital products and other fields due to their high energy density, long cycle life, excellent rate performance, low self-discharge rate and other advantages. With the rapid development of new energy vehicles, higher requirements are placed on the energy density and safety performance of batteries.
[0003] In lithium-ion batteries, the diaphragm is a key component, and its main function is to isolate the positive and negative electrodes to prevent short circuits, while allowing lithium ions to migrate freely in the electrolyte, thereby achieving normal charging and discharging of the battery. An ideal diaphragm should only allow lithium ions to migrate between the positive and negative electrodes. However, the widely used polyethylene and polypropylene diaphragms and their modified or coated products cannot yet achieve single selective conduction for lithium ions. As the battery operates, metal ions such as nickel ions (Ni²⁺) and manganese ions (Mn²⁺) in the positive electrode material will pass through the diaphragm, causing the battery capacity to gradually decay. Therefore, the performance of traditional lithium-ion batteries will significantly decrease after 2 to 3 years of use or after multiple cycles. Although the existing modified or coated diaphragms have improved in heat resistance and mechanical properties, they still cannot achieve selective permeation of lithium ions.
[0004] Therefore, developing a separator that can conduct only lithium ions and prevent the migration of metal ions such as nickel and manganese is of great significance for improving the performance of lithium-ion batteries and extending their service life. Summary of the invention
[0005] In view of the above problems existing in the prior art, the present invention provides a polyolefin coated diaphragm with ion selectivity, a preparation method and application thereof. The specific invention contents are as follows: In a first aspect, the present invention provides a polyolefin coated diaphragm with ion selectivity, wherein the polyolefin coated diaphragm is composed of a porous polyolefin support layer, and a first ion selective cortex and a second ion selective cortex located on both sides of the porous polyolefin support layer; the first ion selective cortex and the second ion selective cortex both contain an intrinsic microporous polymer PIM or a modified intrinsic microporous polymer PIM; wherein, The first ion-selective cortex and the second ion-selective cortex have the same or different compositions.
[0006] Optionally, the intrinsic microporous polymer PIM is selected from PIM-1 or PIM-2, and the modified intrinsic microporous polymer PIM is selected from one or more of PIM-PI, PIM-CA, PIM-EN, PIM-EA-TB, PIM-Trip-TB and PIM-TOT, and the structural formula is as follows: , , , , , , , ; The value of n satisfies the requirement that the molecular weight of the intrinsic microporous polymer PIM or the modified intrinsic microporous polymer PIM is between 50,000 and 100,000.
[0007] Optionally, the thickness T of the porous polyolefin support layer is 2 is 5 μm to 25 μm, and the thickness T of the first ion selective cortex is 1 The thickness of the second ion selective cortex is 0.5 μm to 2 μm. 3 It is 0.1μm~1μm.
[0008] Optionally, the thickness T of the first ion selective cortex is 1 , the thickness T of the porous polyolefin support layer 2 The thickness of the second ion selective cortex T 3 Between 2 / 20≤T 1 <(T 3 +T 2 ) 0.5 ; The thickness T of the first ion selective cortex 1 The thickness of the second ion selective cortex is T 3 Between 1 / 4≤T 3 ≤T 1 / 2.
[0009] Optionally, the porous polyolefin support layer is composed of polyethylene and / or polypropylene, and has a porosity of 40% to 50%.
[0010] Optionally, the water content of the polyolefin coated diaphragm is 530-620 ppm.
[0011] Optionally, the electrolyte wetting area of the polyolefin coated diaphragm is 74.1 to 85.4 mm 2 .
[0012] Optionally, the surface density of the polyolefin coated diaphragm is 8.11 to 8.45 g / m 2 .
[0013] Optionally, the polyolefin coated diaphragm has a heat shrinkage rate of 3.5% to 4.8% under the condition of being kept at 150° C. for 1 hour.
[0014] Optionally, the diffusion coefficient of the polyolefin coated diaphragm for nickel ions is 1.19×10 -9 ~2.57×10 -9 cm 2 / s.
[0015] Optionally, the diffusion coefficient of the polyolefin coated membrane to manganese ions is 2.32×10 -10 ~ 3.78×10 - 10 cm 2 / s.
[0016] In a second aspect, the present invention provides a method for preparing the polyolefin coated diaphragm with ion selectivity as described in the first aspect, the preparation method comprising: Coating the first slurry on one side of the porous polyolefin support layer, and forming a first ion selective cortex on the one side of the porous polyolefin support layer after drying; Coating the second slurry on the other side of the porous polyolefin support layer, and forming a second ion selective cortex on the other side of the porous polyolefin support layer after drying, thereby completing the preparation of the polyolefin coated diaphragm; Wherein, the first slurry and the second slurry are both formed by dissolving an intrinsic microporous polymer PIM or a modified intrinsic microporous polymer PIM into an organic solvent; The intrinsic microporous polymer PIM or modified intrinsic microporous polymer PIM contained in the first slurry and the second slurry are the same or different.
[0017] Optionally, in the first slurry and the second slurry, the organic solvent is selected from one or more of N-methylpyrrolidone, dimethyl sulfoxide, N,N-dimethylformamide, N,N-dimethylacetamide and chloroform.
[0018] Optionally, in the first slurry and the second slurry, the mass proportion of the intrinsic microporous polymer PIM or the modified intrinsic microporous polymer PIM is 20% to 30%.
[0019] Optionally, the temperature required for the drying is 50-100°C; The coating is selected from any one of spray coating, blade coating and dip coating.
[0020] In a third aspect, the present invention provides an application of a polyolefin coated diaphragm having ion selectivity, wherein the polyolefin coated diaphragm described in the first aspect is used as a diaphragm for a lithium ion battery.
[0021] Compared with the prior art, the present invention has the following advantages: The present invention provides a polyolefin coated diaphragm with ion selectivity, which is composed of a porous polyolefin support layer, and a first ion selective cortex and a second ion selective cortex located on both sides of the porous polyolefin support layer; the first ion selective cortex and the second ion selective cortex are both composed of intrinsic microporous polymer PIM or modified intrinsic microporous polymer PIM; PIM materials have high specific surface area, rich microporous structure and good electrolyte affinity; therefore, PIM materials are added on both sides of the porous polyolefin support layer. The first ion-selective cortex and the second ion-selective cortex composed of the above-mentioned materials can effectively improve the overall mechanical properties and heat resistance of the diaphragm without affecting the wettability of the porous polyolefin support layer and the lithium ion permeability, and maintain the lightweight characteristics of the diaphragm; at the same time, it also greatly reduces the diffusion coefficient of the diaphragm to metal ions such as Mn, Ni, and Fe, effectively avoiding the use of existing diaphragms (without ion-selective cortex) in the positive electrode materials of lithium-ion batteries. The metal ions such as Mn, Ni, and Fe are dissolved during battery operation and then contaminate the negative electrode of the battery, which can effectively extend the battery life. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0023] Figure 1 A schematic diagram of the cross-sectional structure of a polyolefin-coated diaphragm with ion selectivity provided in an embodiment of the present invention is shown; Figure 2 A flow chart of a method for coating a polyolefin membrane with ion selectivity provided by an embodiment of the present invention is shown; Figure 3 A physical picture of a polyolefin-coated diaphragm with ion selectivity provided in an embodiment of the present invention is shown. DETAILED DESCRIPTION
[0024] The technical solutions in the embodiments of the present invention will be described clearly and completely below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, not all of the embodiments. The following description of at least one exemplary embodiment is actually only illustrative and is by no means a limitation on the present invention and its application or use. Based on the embodiments of the present invention, any product identical or similar to the present invention obtained by anyone under the inspiration of the present invention or by combining the features of the present invention with other prior arts falls within the scope of protection of the present invention. In addition, all other embodiments obtained by ordinary technicians in this field without carrying out creative work belong to the scope of protection of the present invention.
[0025] In the embodiment, no specific experimental steps or conditions are indicated, and the operation or conditions of the conventional experimental steps described in the prior art in this field can be carried out. The reagents used and other instruments that do not indicate the manufacturer are conventional reagent products that can be obtained commercially. In addition, the accompanying drawings are only schematic diagrams of the embodiments of the present invention and are not necessarily drawn to scale. The same reference numerals in the figures represent the same or similar parts, and thus their repeated description will be omitted. Some block diagrams shown in the accompanying drawings are functional entities and do not necessarily correspond to physically or logically independent entities.
[0026] Technologies, methods, and equipment known to ordinary technicians in the relevant field may not be discussed in detail, but where appropriate, the technologies, methods, and equipment should be considered as part of the description of the present invention.
[0027] In the description of the present invention, it should be understood that the use of terms such as "first" and "second" to limit components is only for the convenience of distinguishing the corresponding components. Unless otherwise stated, the above terms have no special meaning and therefore cannot be understood as limiting the scope of protection of the present invention.
[0028] In addition, the technical features involved in the different embodiments of the present invention described below can be combined with each other as long as they do not conflict with each other.
[0029] It should be noted that, in the intrinsic microporous polymer PIM involved in the embodiment of the present invention, PIM-1 is specifically prepared by polymerization of 5,5',6,6'-tetrahydroxy-3,3,3,3'-tetramethyl-1,1'-spironitrile (TTSBI) and 2,3,5,6-tetrafluorohydroquinone (TFTPN); the reaction formula is as follows: , where the value of n is such that the molecular weight of PIM-1 is between 50,000 and 100,000.
[0030] PIM-2 is synthesized by polymerization of TTSBI and perfluorobiphenyl (DFBP), and the reaction formula is as follows: , where the value of n is such that the molecular weight of PIM-2 is between 50,000 and 100,000.
[0031] In the modified intrinsic microporous polymer PIM involved in the embodiment of the present invention, PIM-PI is prepared by using pyromellitic dianhydride (PMDA) and spiroindene diamine (SBF) as monomers to form a polyimide precursor (polyamic acid) through a polycondensation reaction, and then imidization; the reaction formula is as follows: , where the value of n satisfies the requirement that the molecular weight of PIM-PI is between 50,000 and 100,000.
[0032] PIM-CA is a carboxylated derivative of PIM-1, with the structural formula: , where the value of n is such that the molecular weight of PIM-CA is between 50,000 and 100,000.
[0033] PIM-EN is based on the copolymerization of 2.4 2',3',6',7'-tetrahydroxyfluorene derivative [fluorene-9,9'-anthracene-10',9'-fluorene] (EN), TTSBI and TFTPN. The reaction formula is as follows: , where the value of n satisfies the requirement that the molecular weight of PIM-EN is between 50,000 and 100,000.
[0034] PIM-EA-TB is based on the alternating polymerization of ethanethracene diamine (EA) and tereug base (TB), and PIM-Trip-TB is based on the alternating polymerization of triptylenediamine (Trip) and tereug base (TB). The reaction formula is as follows: , where the value of n satisfies the requirement that the molecular weight of PIM-EA-TB is between 50,000 and 100,000.
[0035] , where the value of n satisfies the requirement that the molecular weight of PIM-Trip-TB is between 50,000 and 100,000.
[0036] PIM-TOT is formed by polycondensation of 5,5',6,6'-tetrahydroxy-3,3,3,3'-tetramethyl-1,1'-spironitrile (TTSBI) and 2,3,7,8-tetrafluoro-5,5',10,10'-tetraoxythioanthracene (TOT) monomers. The reaction formula is as follows: , where the value of n satisfies the requirement that the molecular weight of PIM-TOT is between 50,000 and 100,000.
[0037] In a first aspect, the present invention provides a polyolefin-coated diaphragm having ion selectivity, Figure 1FIG. 4 shows a schematic cross-sectional structure diagram of a polyolefin-coated diaphragm with ion selectivity provided by an embodiment of the present invention, such as Figure 1 As shown, the polyolefin coated membrane is composed of a porous polyolefin support layer 101, and a first ion selective cortex 102 and a second ion selective cortex 103 located on both sides of the porous polyolefin support layer 101; the first ion selective cortex 102 and the second ion selective cortex 103 both include intrinsic microporous polymer PIM or modified intrinsic microporous polymer PIM; in the first ion selective cortex, the selection of intrinsic microporous polymer PIM or modified intrinsic microporous polymer PIM is the same as or different from the selection of intrinsic microporous polymer PIM or modified intrinsic microporous polymer PIM in the second ion selective cortex.
[0038] In a specific implementation, the intrinsic microporous polymer PIM selected in the present invention is selected from PIM-1 or PIM-2, and the modified intrinsic microporous polymer PIM is selected from one or more of PIM-PI, PIM-CA, PIM-EN, PIM-EA-TB, PIM-Trip-TB and PIM-TOT. Since PIM materials have a high specific surface area, rich microporous structure and good electrolyte affinity, the embodiment of the present invention deposits an intrinsic microporous polymer PIM or a modified intrinsic microporous polymer PIM of suitable thickness on the porous polyolefin support. The two sides of the support layer (forming the first ion-selective cortex and the second ion-selective cortex) do not affect the wettability and lithium ion permeability of the porous polyolefin support layer, and maintain the lightweight characteristics of the diaphragm, and also improve the overall mechanical properties and heat resistance of the diaphragm; at the same time, it also greatly reduces the diffusion coefficient of the diaphragm to metal ions such as Mn, Ni, and Fe, and effectively avoids the use of existing diaphragms (without ion-selective cortex) in the positive electrode materials of lithium-ion batteries. The metal ions such as Mn, Ni, and Fe are dissolved during battery operation and then contaminate the negative electrode of the battery, which can effectively extend the battery life.
[0039] The structural formula of the intrinsic microporous polymer PIM or the modified intrinsic microporous polymer PIM used in this embodiment is shown below: , , , , , , , ; wherein the value of n satisfies the requirement that the molecular weight of the intrinsic microporous polymer PIM is between 50,000 and 100,000.
[0040] Furthermore, the specific compositions of the first ion-selective cortex and the second ion-selective cortex may be the same or different; as an example, the first ion-selective cortex may be composed of an intrinsic microporous polymer PIM (such as PIM-1), and the second ion-selective cortex may be composed of a modified intrinsic microporous polymer PIM (such as PIM-PI).
[0041] Furthermore, in order to ensure that the polyolefin coated diaphragm has good wettability, lithium ion permeability and diffusion coefficient for metal ions such as Mn, Ni, and Fe, the embodiment of the present invention is based on a thickness T 2 The porous polyolefin membrane with a thickness of 5 μm to 25 μm is used as the intermediate support layer, and the thickness of the first ion selective skin layer is T 1 The thickness of the second ion selective cortex is 0.5 μm to 2 μm. 3 The thickness of the first ion selective cortex is 0.1 μm to 1 μm, and the first ion selective cortex and the second ion selective cortex are coated and prepared. After a large number of performance tests, it is found that the thickness of the first ion selective cortex T 1 , the thickness of the porous polyolefin support layer T 2 and the thickness of the second ion-selective cortex T 3 Between 2 / 20≤T 1 <(T 3 +T 2 ) 0.5 , and the thickness of the first ion-selective cortex is T 1 and the thickness of the second ion-selective cortex T 3 Between 1 / 4≤T 3 ≤T 1 / 2, the water content of the polyolefin coated separator obtained was 530-620 ppm, the electrolyte infiltration area was 74.1-85.4, and the surface density was 8.11-8.45 g / m 2 ; The diffusion coefficient of nickel ions in the polyolefin-coated diaphragm is 1.19×10 -9 ~ 2.57×10 -9 cm 2 / s, and the diffusion coefficient of polyolefin-coated diaphragm to manganese ions is 2.32×10 -10 ~ 3.78×10 -10 cm 2 / s; and, the thermal shrinkage rate of the polyolefin coated diaphragm is 3.5% to 4.8% under the condition of keeping warm at 150°C for 1 hour, meeting the excellent performance requirements.
[0042] In some embodiments, the porous polyolefin support layer is composed of polyethylene and / or polypropylene, and has a porosity of 40% to 50%.
[0043] In a second aspect, the present invention provides a method for preparing a polyolefin-coated diaphragm having ion selectivity. Figure 2 The flow chart of the preparation method of the polyolefin coated diaphragm with ion selectivity provided by the embodiment of the present invention is shown as follows: Figure 2 As shown, the preparation method comprises the following steps: S1, coating a first slurry on one side of a porous polyolefin support layer, and forming a first ion selective cortex on one side of the porous polyolefin support layer after drying; S2, coating the second slurry on the other side of the porous polyolefin support layer, forming a second ion selective skin layer on the other side of the porous polyolefin support layer after drying, and completing the preparation of the polyolefin coated diaphragm.
[0044] In the embodiment of the present invention, the ion selective cortex is prepared on both sides of the porous polyolefin support layer by slurry coating. The composition of the porous polyolefin support layer selected in this embodiment can be polyethylene or polypropylene, or a mixture of polyethylene and polypropylene. The porosity of the porous polyolefin support layer is 40% to 50%; The first slurry and the second slurry used in the embodiments of the present invention are both formed by dissolving an intrinsic microporous polymer PIM in an organic solvent; the intrinsic microporous polymer PIM is selected from PIM-1 or PIM-2; the modified intrinsic microporous polymer PIM is selected from one or more of PIM-PI, PIM-CA, PIM-EN, PIM-EA-TB, PIM-Trip-TB and PIM-TOT; and the intrinsic microporous polymer PIM or modified intrinsic microporous polymer PIM contained in the first slurry and the second slurry may be the same or different. As an example, the first slurry and the second slurry are both formed by dissolving an intrinsic microporous polymer PIM (such as PIM-1) in an organic solvent; the first slurry and the second slurry can also be formed by dissolving a modified intrinsic microporous polymer PIM (such as PIM-PI) in an organic solvent; or the first slurry is formed by dissolving an intrinsic microporous polymer PIM (such as PIM-1) in an organic solvent, and the second slurry is formed by dissolving an intrinsic microporous polymer PIM (such as PIM-1) in an organic solvent.
[0045] In this embodiment, in order to avoid the rapid volatilization of the solvent, which leads to the problem of uneven thickness of the first ion-selective cortex and the second ion-selective cortex formed by coating, when preparing the slurry, the solvent needs to be an organic solvent with moderate volatility. The organic solvent used in this embodiment can be selected from one or more of N-methylpyrrolidone (NMP), dimethyl sulfoxide (DMSO), N,N-dimethylformamide (DMF), N,N-dimethylacetamide (DMAc) and chloroform.
[0046] In this embodiment, the mass proportion of the intrinsic microporous polymer PIM or the modified intrinsic microporous polymer PIM in the slurry is adjusted to 20% to 30%, so that the slurry has the appropriate viscosity (100-1000 mPa·s) required for coating, and the slurry is successfully adhered to both sides of the porous polyolefin support layer by coating. In addition, the control of the slurry coating thickness is a key parameter that needs to be regulated in the preparation of polyolefin coated diaphragms, which directly affects the final performance of the polyolefin coated diaphragm, such as ionic conductivity, mechanical strength, electrolyte wettability, and diffusion coefficients for manganese and nickel ions; the thickness T of the porous polyolefin support layer selected in this embodiment is 2 The thickness of the first ion selective cortex is 5 μm to 25 μm. 1 The thickness of the second ion selective cortex is 0.5 μm to 2 μm. 3 A large number of experimental studies have found that the coating thickness of the first ion selective cortex T 1 , the coating thickness T of the porous polyolefin support layer 2 The coating thickness T of the second ion selective cortex is 3 Between 2 / 20≤T 1 <(T 3 +T 2 ) 0.5 ; The coating thickness T of the first ion selective cortex 1 The coating thickness T of the second ion selective cortex is 3 Between 1 / 4≤T 3 ≤T 1 / 2. To ensure that the thickness of the ion-selective cortex is moderate (too thick will reduce ion conductivity, too thin may affect mechanical strength and electrolyte wettability).
[0047] During the specific implementation, in the slurry coating process, the control of the coating thickness also needs to comprehensively consider factors such as slurry concentration, slurry viscosity, coating method and drying conditions. After the coating of the first ion-selective cortex is completed in this embodiment, a gradient temperature rise drying method is used to dry it to avoid the rapid volatilization of the solvent causing shrinkage or blistering of the coating. The gradient temperature rise method includes: drying at 50 ° C for 30-60 min, then heating to 80 ° C for drying for 30-40 min, and continuing to heat to 100 ° C for drying for 30 min. Similarly, after the coating of the second ion-selective cortex is completed in this embodiment, a gradient temperature rise drying method is continued to be used to dry it to avoid the rapid volatilization of the solvent causing shrinkage or blistering of the coating. The gradient temperature rise method includes: drying at 50 ° C for 30-60 min, then heating to 80 ° C for drying for 30-40 min, and continuing to heat to 100 ° C for drying for 30 min.
[0048] In order to enable those skilled in the art to more clearly understand the present invention, the polyolefin coated diaphragm with ion selectivity, the preparation method and the application of the present invention are now described in detail through the following examples.
[0049] The synthesis process of the PIM materials used in the following examples is as follows: PIM-1 (number average molecular weight of about 100,000, preparation process reference Journal of Membrane Science 333 (2009) 125–131): DMAc was added to a three-necked flask, protected with nitrogen, KOH was added as a catalyst, and stirred to mix. Then the above TTSBI monomer was slowly added to the solvent, and after it was completely dissolved, an equal molar amount of TFTPN was gradually added. The reaction mixture was heated to 165 °C and stirred for 48 hours. After the reaction was completed, it was transferred to 100 mL of neutral water for separation. The reaction mixture was added to methanol for precipitation to obtain a crude polymer PIM-1. The precipitate was washed with deionized water several times to remove the solvent residue and unreacted small molecular monomers, and then dried in a suction filtration device. The obtained crude precipitate was placed in a vacuum drying oven and dried at 60 °C until a completely dry yellow powder or glassy polymer block was formed (IR spectrum analysis showed the appearance of C≡N (2200 cm⁻¹) and benzene ring characteristic peaks (1600 cm⁻¹), which confirmed the molecular skeleton; nuclear magnetic resonance (NMR) was used to further confirm the phenyl, tetramethyl and cyano structures on the main chain).
[0050] PIM-CA (number average molecular weight is about 80,000, preparation process reference: Adv Sustain Syst 2018;2(10):1800044.): PIM-1 was placed in a 20% potassium hydroxide ethanol / water (volume ratio 1.5 / 1) solution, heated to 100°C, and reacted for 20 hours. After the reaction was completed, the alkalinity was neutralized with excess acetic acid, filtered and washed with methanol to obtain a preliminary hydrolysis product. The preliminary hydrolysis product was added to a sulfuric acid / water / acetic acid (volume ratio 2.5 / 2 / 1) solution, heated to 120°C, and reacted for 10 hours. After cooling to room temperature, the mixture was poured into excess water, filtered and washed with methanol to obtain a green powder. The powder was placed in a vacuum drying oven and dried at 80°C to obtain the final product COOH-PIM-1.
[0051] PIM-EA-TB (number average molecular weight of about 80,000, preparation process reference: Polymer 236 (2021) 124295): Ethane anthracene diamine (EA) and tereuglycine (TB) monomers were dissolved in chloroform in a certain ratio (1:1 molar ratio) to form a uniform solution. The mass fraction was 20%, and the above mixed solution was placed in a reactor, and 1% toluenesulfonic acid was added to promote the polymerization reaction. Under nitrogen protection, the reactor was heated to 60°C, and the reaction time was 24 hours. The monomers formed PIM-EA-TB polymers through polycondensation. After the reaction was completed, the reaction mixture was poured into a large amount of cold ethanol to precipitate the polymer. The precipitated polymer was collected by suction filtration and washed with ethanol several times to remove unreacted monomers and catalysts. The washed polymer was dried in a vacuum drying oven at 60°C for 24 hours to obtain a pure PIM-EA-TB polymer.
[0052] PIM-TOT (number average molecular weight is about 100,000, reference J. Mater. Chem. A, 2021, 9, 2840–2849): DMF was added to a three-necked flask, protected with nitrogen, KOH was added as a catalyst, and stirred to mix. Then TTSBI monomer was slowly added to the solvent, and after it was completely dissolved, an equimolar amount of TOT was gradually added. The reaction mixture was heated to 180 °C and stirred for 40 hours. After the reaction was completed, it was transferred to water for separation. The reaction mixture was added to ethanol for precipitation, and the precipitate was washed with deionized water several times to remove the solvent residue and unreacted small molecular monomers, and then dried in a suction filtration device. The obtained crude precipitate was placed in a vacuum drying oven and dried at 80 °C to finally obtain PIM-TOT.
[0053] PIM-PI (number average molecular weight is about 90,000, preparation process reference: ACS Appl. Polym. Mater. 2023,5, 1420−1429): PMDA and SBF are dissolved in DMAc at a molar ratio of 1:1. Under nitrogen protection, the reaction mixture is slowly stirred at 0℃~5℃ for 1-2 hours to ensure that the monomer is fully dissolved. Then it is warmed to room temperature and reacted for 48 hours. After the reaction is completed, it is transferred to water for separation. The reaction mixture is added to ethanol for precipitation, and the precipitate is washed with deionized water several times to remove the solvent residue and unreacted small molecular monomers, and then dried in a suction filtration device. The obtained crude precipitate is placed in a vacuum drying oven and dried at 80℃ to finally obtain PIM-PI.
[0054] PIM-EN (number average molecular weight is about 70,000, preparation process reference: J Membr Sci 2021; 629: 119284.): TTSBI, TFTPN and EN (1:1:1 molar ratio) were dissolved in chloroform to form a uniform solution with a mass fraction of 30%. Under nitrogen protection, it was heated to 160°C and the reaction time was 48 hours. The monomer formed a PIM-EN polymer by polycondensation. After the reaction was completed, the reaction mixture was poured into a large amount of cold ethanol to precipitate the polymer. The precipitated polymer was collected by suction filtration and washed with ethanol several times to remove unreacted monomers. The washed polymer was dried in a vacuum drying oven at 80°C for 24 hours to obtain a pure PIM-EN polymer.
[0055] PIM-Trip-TB (number average molecular weight of about 90,000, preparation process reference: J Membr Sci 2023;677:121614.): Terreger base (TB) and triptylenediamine (Trip) (1:1 molar ratio) were dissolved in chloroform to form a uniform solution with a mass fraction of 20%. Under nitrogen protection, it was heated to 100°C and the reaction time was 48 hours. The monomers formed PIM-Trip-TB polymers through polycondensation. After the reaction was completed, the reaction mixture was poured into a large amount of cold ethanol to precipitate the polymer. The precipitated polymer was collected by suction filtration and washed with ethanol several times to remove unreacted monomers. The washed polymer was dried in a vacuum drying oven at 100°C for 24 hours to obtain a pure PIM-Trip-TB polymer.
[0056] Example 1 A polyethylene membrane (model EG803J, Shanghai Enjie) with a thickness of 5 μm and a porosity of 40% was selected as the porous polyolefin support layer. The first slurry was coated on one side of the porous support layer using a coating machine. After coating, it was dried at 50 °C for 30 min, then heated to 80 °C for 40 min, and then heated to 100 °C for 30 min. After drying, the first ion-selective skin layer was formed. The second slurry was coated on the other side of the porous polyolefin support layer using a coating machine. After coating, it was dried at 50°C for 30 min, then heated to 80°C for 40 min, and then heated to 100°C for 30 min. After drying, a second ion-selective cortex was formed, and a polyolefin-coated diaphragm with ion selectivity was obtained. The first slurry and the second slurry have the same composition, both of which are formed by dissolving PIM-1 in an organic solvent of N,N-dimethylacetamide (DMAc). In the first slurry and the second slurry, the mass proportion of PIM-1 is 30%; The overall thickness of the obtained polyolefin coated membrane is 8 μm, and the thickness of the first ion selective skin layer is T 1is 2 μm, and the thickness of the second ion-selective cortex is T 3 is 1 μm, and the thickness of the first ion-selective cortex is T 1 , the thickness of the porous polyolefin support layer T 2 (=5 μm) and the thickness of the second ion-selective cortex T 3 The formula T is satisfied between 2 / 20≤T 1 <(T 3 +T 2 ) 0.5 , the actual picture is as follows Figure 3 shown.
[0057] Example 2 A polypropylene membrane (model EG701M, Shanghai Enjie) with a thickness of 10 μm and a porosity of 48% was selected as the porous polyolefin support layer. The first slurry was sprayed on one side of the porous polyolefin support layer using a spraying device. After spraying, the membrane was dried at 50°C for 30 min, then heated to 80°C for 40 min, and then heated to 100°C for 30 min. After drying, the first ion-selective skin layer was formed. Continue to spray the second slurry on the other side of the porous polyolefin support layer. After spraying, dry it at 50 °C for 30 minutes, then heat it to 80 °C for 40 minutes, and continue to heat it to 100 °C for 30 minutes. After drying, the second ion-selective skin layer is formed, and a polyolefin-coated diaphragm with ion selectivity is obtained. Among them, the first slurry and the second slurry have the same composition, both of which are formed by dissolving PIM-CA in N-methylpyrrolidone (NMP) organic solvent, and the mass proportion of PIM-CA is 25%; The overall thickness of the obtained polyolefin coated membrane is 10.75 μm, and the thickness of the first ion selective skin layer is T 1 The thickness of the second ion selective cortex is 0.5 μm. 3 is 0.25 μm, and the thickness of the first ion-selective cortex T 1 , the thickness of the porous polyolefin support layer T 2 (=10 μm) and the thickness of the second ion-selective cortex T 3 The formula T is satisfied between 2 / 20≤T 1 <(T 3 +T 2 ) 0.5 .
[0058] Example 3 A polyethylene membrane (model EG811J, Shanghai Enjie) with a thickness of 15 μm and a porosity of 46% was selected as the porous polyolefin support layer; the first slurry was coated on one side of the porous support layer using a coating machine, and after coating, it was dried at 50 °C for 30 min, then heated to 80 °C for 40 min, and then continued to be heated to 100 °C for 30 min; after drying, the first ion selective skin layer was formed; The second slurry was coated on the other side of the porous polyolefin support layer using a coating machine. After coating, it was dried at 50°C for 30 min, then heated to 80°C for 40 min, and then heated to 100°C for 30 min. After drying, a second ion-selective cortex was formed, and a polyolefin-coated diaphragm with ion selectivity was obtained. The first slurry and the second slurry have the same composition, both of which are formed by dissolving PIM-EA-TB in N,N-dimethylacetamide (DMAc). In the first slurry and the second slurry, the mass proportion of PIM-EA-TB is 20%; The overall thickness of the obtained polyolefin coated membrane is 16.05 μm, and the thickness of the first ion selective skin layer is T 1 The thickness of the second ion-selective cortex is 0.75 μm. 3 is 0.3 μm, and the thickness of the first ion-selective cortex is T 1 , the thickness of the porous polyolefin support layer T 2 (=15 μm) and the thickness of the second ion-selective cortex T 3 The formula T is satisfied between 2 / 20≤T 1 <(T 3 +T 2 ) 0.5 .
[0059] Example 4 A polypropylene membrane (model EG714M, Shanghai Enjie) with a thickness of 20 μm and a porosity of 50% was selected as the porous polyolefin support layer; the first slurry was coated on one side of the porous support layer using a coating machine, and after coating, it was dried at 50 °C for 30 min, then heated to 80 °C for 40 min, and then continued to be heated to 100 °C for 30 min; after drying, the first ion-selective skin layer was formed; The second slurry was coated on the other side of the porous polyolefin support layer using a coating machine. After coating, it was dried at 50°C for 30 minutes, then heated to 80°C for 40 minutes, and then heated to 100°C for 30 minutes. After drying, a second ion-selective skin layer was formed, and a polyolefin-coated diaphragm with ion selectivity was obtained. The first slurry and the second slurry have the same composition, both of which are formed by dissolving PIM-TOT in chloroform organic solvent. In the first slurry and the second slurry, the mass proportion of PIM-TOT is 30%; The overall thickness of the obtained polyolefin coated membrane is 21.15 μm, and the thickness of the first ion selective skin layer is T 1 is 1 μm, and the thickness of the second ion-selective cortex is T 3 is 0.15 μm, and the thickness of the first ion-selective cortex T 1 , the thickness of the porous polyolefin support layer T 2 (=20 μm) and the thickness of the second ion-selective cortex T 3 The formula T is satisfied between 2 / 20≤T 1 <(T 3 +T 2 ) 0.5 .
[0060] Example 5 A polyethylene membrane (model EG823J, Shanghai Enjie) with a thickness of 12 μm and a porosity of 48% was selected as the porous polyolefin support layer. The first slurry was coated on one side of the porous support layer using a coating machine. After coating, it was dried at 50 °C for 30 min, then heated to 80 °C for 40 min, and then heated to 100 °C for 30 min. After drying, the first ion-selective skin layer was formed. The second slurry was coated on the other side of the porous polyolefin support layer using a coating machine. After coating, it was dried at 50°C for 30 min, then heated to 80°C for 40 min, and then heated to 100°C for 30 min. After drying, a second ion-selective cortex was formed, and a polyolefin-coated diaphragm with ion selectivity was obtained. The first slurry and the second slurry have the same composition, both of which are formed by dissolving PIM-PI in DMF organic solvent. In the first slurry and the second slurry, the mass proportion of PIM-PI is 28%; The overall thickness of the obtained polyolefin coated membrane is 12.8 μm, and the thickness of the first ion selective skin layer is T 1 is 0.6 μm, and the thickness of the second ion-selective cortex is T 3 is 0.2 μm, and the thickness of the first ion-selective cortex is T 1 , the thickness of the porous polyolefin support layer T 2(=12 μm) and the thickness of the second ion-selective cortex T 3 The formula T is satisfied between 2 / 20≤T 1 <(T 3 +T 2 ) 0.5 .
[0061] Example 6 Compared with Example 1, the difference is that the first slurry and the second slurry provided in this example are both formed by dissolving PIM-EN in an organic solvent of N,N-dimethylacetamide (DMAc), and the mass proportion of PIM-EN in the first slurry and the second slurry is 30%; the rest of the preparation process is the same. The overall thickness of the obtained polyolefin coated membrane is 8 μm, and the thickness of the first ion selective skin layer is T 1 The thickness of the second ion selective cortex is 2 μm. 3 is 1 μm, and the thickness of the first ion-selective cortex is T 1 , the thickness of the porous polyolefin support layer T 2 (=5 μm) and the thickness of the second ion-selective cortex T 3 The formula T is satisfied between 2 / 20≤T 1 <(T 3 +T 2 ) 0.5 .
[0062] Example 7 Compared with Example 1, the difference is that the first slurry and the second slurry provided in this embodiment are both formed by dissolving PIM-Trip-TB in DMAc organic solvent, and the mass proportion of PIM-Trip-TB in the first slurry and the second slurry is 30%; the rest of the preparation process is the same.
[0063] The overall thickness of the obtained polyolefin coated membrane is 8 μm, and the thickness of the first ion selective skin layer is T 1 The thickness of the second ion selective cortex is 2 μm. 3 is 1 μm, and the thickness of the first ion-selective cortex is T 1 , the thickness of the porous polyolefin support layer T 2 (=5 μm) and the thickness of the second ion-selective cortex T 3 The formula T is satisfied between 2 / 20≤T 1 <(T 3 +T 2 ) 0.5 .
[0064] Example 8 Compared with Example 1, the difference is that the first slurry provided in this embodiment is formed by dissolving PIM-TOT and PIM-1 in DMAc organic solvent, and in the first slurry, the mass proportions of PIM-TOT and PIM-1 are both 30%, among which the mass proportion of PIM-TOT is 15%; the second slurry is also formed by dissolving PIM-TOT and PIM-1 in DMAc organic solvent, and in the second slurry, the mass proportions of PIM-TOT and PIM-1 are both 30%, among which the mass proportion of PIM-TOT is 15%; the rest of the processes are the same.
[0065] The overall thickness of the obtained polyolefin coated membrane is 8 μm, and the thickness of the first ion selective skin layer is T 1 The thickness of the second ion selective cortex is 2 μm. 3 is 1 μm, and the thickness of the first ion-selective cortex is T 1 , the thickness of the porous polyolefin support layer T 2 (=5 μm) and the thickness of the second ion-selective cortex T 3 The formula T is satisfied between 2 / 20≤T 1 <(T 3 +T 2 ) 0.5 .
[0066] Example 9 Compared with Example 1, the difference is that the first slurry provided in this embodiment is formed by dissolving PIM-Trip-TB and PIM-1 together in DMAc organic solvent to form a first slurry in which the mass ratio of PIM-Trip-TB and PIM-1 is 30%; wherein the mass ratio of PIM-Trip-TB is 15%; the second slurry is also formed by dissolving PIM-Trip-TB and PIM-TOT together in DMAc organic solvent, in which the mass ratio of PIM-Trip-TB and PIM-TOT is 30%; wherein the mass ratio of PIM-Trip-TB is 15%, and the rest of the processes are the same.
[0067] The overall thickness of the obtained polyolefin coated membrane is 8 μm, the thickness of the first ion selective skin layer is 2 μm, the thickness of the second ion selective skin layer is 1 μm, and the thickness of the first ion selective skin layer is T 1 , the thickness of the porous polyolefin support layer T 2 (=5 μm) and the thickness of the second ion-selective cortex T 3 The formula T is satisfied between 2 / 20≤T 1 <(T 3 +T 2 ) 0.5.
[0068] Example 10 Compared with Example 1, the second slurry of this example is formed by dissolving PIM-PI in an organic solvent of N,N-dimethylacetamide (DMAc), and the mass proportion of PIM-PI is 30%; and in this example, the second slurry is coated on one side of the porous polyolefin support layer to form a second ion selective cortex, and the first slurry (same as Example 1) is still coated on the other side to form a first ion selective cortex. The rest of the process is the same as Example 1.
[0069] The overall thickness of the obtained polyolefin coated membrane is 8 μm, and the thickness of the first ion selective skin layer is T 1 is 2 μm, and the thickness of the second ion-selective cortex is T 3 is 1 μm, and the thickness of the first ion-selective cortex is T 1 , the thickness of the porous polyolefin support layer T 2 (=5 μm) and the thickness of the second ion-selective cortex T 3 The formula T is satisfied between 2 / 20≤T 1 <(T 3 +T 2 ) 0.5 .
[0070] Comparative Example 1 Dissolving PIM-1 in an organic solvent of N,N-dimethylacetamide (DMAc) to form a slurry in which the mass proportion of PIM-1 is 30%; A polyethylene membrane (model EG803J, Shanghai Enjie) with a thickness of 5 μm and a porosity of 40% was selected as the porous polyolefin support layer; the slurry was coated on one side of the porous support layer using a coating machine, and after coating, it was dried at 50 °C for 30 minutes, then heated to 80 °C for 40 minutes, and then continued to be heated to 100 °C for 30 minutes; after drying, a polyolefin coated membrane was obtained. The overall thickness of the obtained polyolefin coated membrane was 7 μm, and the thickness of the ion selective skin formed by coating was 2 μm.
[0071] Comparative Example 2 Compared with Example 1, the difference is that the overall thickness of the obtained polyolefin coated separator is 5.2 μm, the thickness of the first ion selective skin layer is 0.1 μm, and the thickness of the second ion selective skin layer is 0.1 μm.
[0072] Comparative Example 3 Commercial polypropylene lithium-ion battery base film, model SW809I.
[0073] Performance test The thermal shrinkage, electrolyte wetting area, moisture content, and ion permeation rate of the coated diaphragms obtained in Examples 1 to 9 and Comparative Examples 1 to 3 were measured: Heat shrinkage rate: Cut the coated diaphragm into the size of A4 paper, with the long direction as MD direction and the short direction as TD direction. Draw a 100mm×100mm frame in the middle with a pen. Clip 11 pieces of A4 paper on the top and bottom of the diaphragm. Put it into an oven at 150℃ for 60 minutes and take it out. Measure the size of the drawn frame, recorded as L. Heat shrinkage rate = (100-L)%.
[0074] Electrolyte wetting area: Cut the coated diaphragm into 50mm×50mm size, use a micro-injector to take 2uL of electrolyte and drop it vertically on the sample surface, use an industrial camera to measure the size of the electrolyte diffusion area after 5 minutes, and the data obtained is the electrolyte wetting area.
[0075] Moisture content test: In an environment with a dew point less than -40°C, take 1-1.5g of coated diaphragm sample, bake at 120°C for 5 minutes, and use the Karl Fischer method to test the moisture content in the coated diaphragm.
[0076] The surface density and ion diffusion coefficient are tested according to the standard test methods; surface density: GB / T 30428.1-2013; ion diffusion coefficient: GB / T 30428.1-2013.
[0077] The test results are shown in Table 1 below.
[0078] Table 1 Diaphragm performance test results
[0079] It can be seen from the test results shown in Table 1 that the thickness T2 of the porous polyolefin support layer in Examples 1 to 10 is 5 μm to 25 μm; the thickness T1 of the first ion selective skin layer, the thickness T2 of the porous polyolefin support layer and the thickness T3 of the second ion selective skin layer satisfy T2 / 20≤T1<(T3+T2) 0.5 The thickness T1 of the first ion selective cortex and the thickness T3 of the second ion selective cortex satisfy T1 / 4≤T3≤T1 / 2; the obtained polyolefin coated diaphragm has a moisture content of 530-620 ppm, an electrolyte infiltration area of 74.1-85.4, and a surface density of 8.11-8.45 g / m 2 ; The diffusion coefficient of nickel ions in the polyolefin-coated diaphragm is 1.19×10 -9 ~ 2.57×10 -9 cm 2 / s, and the diffusion coefficient of polyolefin-coated diaphragm to manganese ions is 2.32×10 -10 ~ 3.78×10-10 cm 2 / s; and, the thermal shrinkage of the polyolefin coated diaphragm is 3.5% to 4.8% when kept at 150°C for 1 hour.
[0080] It can be seen from the test results of Example 1 and Comparative Examples 1 and 2 that when the thickness of the first ion selective cortex (T1), the second ion selective cortex (T3) and the porous polyolefin support layer T2 does not satisfy T2 / 20≤T1<(T3+T2) 0.5 , T1 / 4≤T3≤T1 / 2, the various performance data of Comparative Example 2 are significantly lower than those of Example 1 and Comparative Example 1; from the test results of Comparative Examples 1-10 and Comparative Example 3, it can be seen that the polyolefin coated diaphragm provided by the embodiments of the present invention is superior to commercial diaphragms in various performance tests.
[0081] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification.
[0082] For the method embodiments, for the sake of simplicity, they are all described as a series of action combinations, but those skilled in the art should know that the present invention is not limited by the order of the actions described, because according to the present invention, some steps can be performed in other orders or simultaneously. Secondly, those skilled in the art should also know that the embodiments described in the specification are all preferred embodiments, and the actions and components involved are not necessarily required by the present invention.
[0083] The above is a detailed introduction to a polyolefin coated diaphragm with ion selectivity, a preparation method and an application provided by the present invention. Specific examples are used in this article to illustrate the principles and implementation methods of the present invention. The description of the above embodiments is only used to help understand the method of the present invention and its core idea; at the same time, for general technicians in this field, according to the ideas of the present invention, there will be changes in the specific implementation methods and application scopes. In summary, the content of this specification should not be understood as a limitation on the present invention.
Claims
1. A polyolefin-coated diaphragm having ion selectivity, characterized in that: The polyolefin coated diaphragm is composed of a porous polyolefin support layer, and a first ion selective skin layer and a second ion selective skin layer located on both sides of the porous polyolefin support layer; the first ion selective skin layer and the second ion selective skin layer both contain an intrinsic microporous polymer PIM or a modified intrinsic microporous polymer PIM; wherein, The first ion-selective cortex and the second ion-selective cortex have the same or different compositions.
2. The polyolefin-coated diaphragm with ion selectivity according to claim 1, characterized in that: The intrinsic microporous polymer PIM is selected from PIM-1 or PIM-2, and the modified intrinsic microporous polymer PIM is selected from one or more of PIM-PI, PIM-CA, PIM-EN, PIM-EA-TB, PIM-Trip-TB and PIM-TOT, and the structural formula is as follows: 、 、 、 、 、 、 、 ; In the structural formula, the value of n satisfies that the molecular weight of the intrinsic microporous polymer PIM or the modified intrinsic microporous polymer PIM is between 50,000 and 100,000.
3. The polyolefin-coated diaphragm with ion selectivity according to claim 1, characterized in that: The thickness T2 of the porous polyolefin support layer is 5 μm to 25 μm, the thickness T1 of the first ion selective skin layer is 0.5 μm to 2 μm, and the thickness T3 of the second ion selective skin layer is 0.1 μm to 1 μm.
4. The polyolefin coated diaphragm with ion selectivity according to claim 3, characterized in that: The thickness T1 of the first ion selective skin layer, the thickness T2 of the porous polyolefin support layer and the thickness T3 of the second ion selective skin layer satisfy T2 / 20≤T1<(T3+T2) 0.5 ; The thickness T1 of the first ion selective cortex and the thickness T3 of the second ion selective cortex satisfy T1 / 4≤T3≤T1 / 2.
5. The polyolefin coated diaphragm with ion selectivity according to claim 1, characterized in that: The porous polyolefin support layer is composed of polyethylene and / or polypropylene, and has a porosity of 40% to 50%.
6. The polyolefin coated diaphragm with ion selectivity according to claim 1, characterized in that: The water content of the polyolefin coated diaphragm is 530-620 ppm.
7. The polyolefin coated diaphragm with ion selectivity according to claim 1, characterized in that: The electrolyte wetting area of the polyolefin coated diaphragm is 74.1 to 85.4 mm 2 .
8. The polyolefin coated diaphragm with ion selectivity according to claim 1, characterized in that: The surface density of the polyolefin coated diaphragm is 8.11-8.45 g / m 2 .
9. The polyolefin coated diaphragm with ion selectivity according to claim 1, characterized in that: The polyolefin coated diaphragm has a heat shrinkage rate of 3.5% to 4.8% under the condition of being kept at 150°C for 1 hour.
10. The polyolefin coated diaphragm with ion selectivity according to claim 1, characterized in that: The diffusion coefficient of the polyolefin-coated diaphragm for nickel ions is 1.19×10 -9 ~2.57×10 -9 cm 2 / s.
11. The polyolefin coated diaphragm with ion selectivity according to claim 1, characterized in that: The diffusion coefficient of the polyolefin coated membrane to manganese ions is 2.32×10 -10 ~ 3.78×10 -10 cm 2 / s.
12. A method for preparing the polyolefin coated diaphragm with ion selectivity as claimed in any one of claims 1 to 11, characterized in that: The preparation method comprises: Coating the first slurry on one side of the porous polyolefin support layer, and forming a first ion selective cortex on the one side of the porous polyolefin support layer after drying; Coating the second slurry on the other side of the porous polyolefin support layer, and forming a second ion selective cortex on the other side of the porous polyolefin support layer after drying, thereby completing the preparation of the polyolefin coated diaphragm; Wherein, the first slurry and the second slurry are both formed by dissolving an intrinsic microporous polymer PIM or a modified intrinsic microporous polymer PIM into an organic solvent; The intrinsic microporous polymer PIM or modified intrinsic microporous polymer PIM contained in the first slurry and the second slurry are the same or different.
13. The method for preparing the polyolefin coated diaphragm with ion selectivity according to claim 12, characterized in that: In the first slurry and the second slurry, the organic solvent is selected from one or more of N-methylpyrrolidone, dimethyl sulfoxide, N,N-dimethylformamide, N,N-dimethylacetamide and chloroform.
14. The method for preparing the polyolefin coated diaphragm with ion selectivity according to claim 12, characterized in that: In the first slurry and the second slurry, the mass proportion of the intrinsic microporous polymer PIM or the modified intrinsic microporous polymer PIM is 20% to 30%.
15. The method for preparing the polyolefin coated diaphragm with ion selectivity according to claim 12, characterized in that: The temperature required for the drying is 50-100°C; The coating is selected from any one of spray coating, blade coating and dip coating.
16. An application of a polyolefin coated diaphragm having ion selectivity, characterized in that: The polyolefin coated separator according to any one of claims 1 to 11 is used as a separator for lithium ion batteries.
Citation Information
Patent Citations
Triptycene-based dianhydrides, polyimides, methods of making each, and methods of use
CN105263989A
Electrochemical cells with ionic sequestration provided by porous separators
CN109804496A
Polyimide coating modified polyolefin composite diaphragm and preparation method thereof
CN113969006A
Lithium ion battery and preparation method thereof
CN114024097A
Battery diaphragm as well as preparation method and application thereof in lithium ion battery
CN119401060A
Cited By
Composite diaphragm, preparation method thereof and secondary battery
CN120341506A
Composite diaphragm and preparation method thereof, and secondary battery
CN120341506B
Single-side coated diaphragm as well as preparation method and application thereof
CN120357146A
Negative pole piece, electrochemical device and preparation method of negative pole piece
CN120497280A